Liver histopathology of broiler chicken (Gallus domesticus): A veterinary forensic model 48 h postmortem - Az Zahra, Shafiyyah; Harlina, Eva; Subangkit, Mawar; Wiranti, Rahayu Woro; Priosoeryanto, Bambang Pontjo (ARSHI Veterinary Letters, 2023)
Veterinary forensic science has not received adequate attention in Indonesia; therefore, its development needs to increase. This research aimed to study veterinary forensic science through histopathology of broiler chicken livers 48 h after death. Seventy-five broiler chickens aged 7 days were euthanized and divided into 25 groups based on post-euthanasia necropsy (n=3). Chicken cadavers were necropsied every 2 h postmortem, and livers were collected to prepare histopathological sections and stained with haematoxylin-eosin (HE). Liver histopathology evaluation and the results obtained were analysed using ImageJ software version 1.53a. The relationship between histopathological variables and postmortem time was analysed using the Pearson’s method. The results showed that decay began at the 18th h postmortem which was marked by the number of hepatocyte cell nuclei. At the 20th hour, putrefactive bacteria were found, and at the 22nd hour, there was an increase in the distance between the hepatocytes. Based on the Pearson correlation value, the number of hepatocyte cell nuclei, the distance between hepatocytes, and the presence of putrefactive bacteria have a strong to very strong relationship with postmortem time; therefore, these results can be used to determine the time of death (postmortem interval)